TELEVISI DAN POLA PIKIR REMAJA PEREMPUAN SINJAI SELATAN - Harmin Hatta; Herdianto Herdianto (Ilmu Komunikasi UIN Alauddin Makassar, 2019)
This study aims to determine the effect of the Love Bell Movie Series on ANTV on the mindset of teenage girls in Songing Village, South Sinjai District. This research uses a quantitative approach with primary and secondary data sources. Data analysis techniques using simple linear regression analysis to determine whether there is influence between two variables, namely the dependent and independent variables. The results showed that the Love Bells Film was obtained by a table with a significance level of 5%, obtained a value of 1,997 and tcount had a value of 3,578 so tcount > ttable. So Ha was accepted and Ho was rejected. Meanwhile based on R square from the previous calculation results is 0.167 which is at the value of 0.00-0.199. This proves that the influence of the Love Bell Film is still very low. This study only obtained 16.8% of the influence of the Love Bell Film on the mindset of adolescent girls, the remaining 83.3% was influenced by other factors not summarized in this analysis.The implication in this research is that the film production party can provide a decent show for the audience and parents so that it can control and supervise the activities of their children who are still in the period of searching for identity.